Examining social networking continuance intention to use from the perspectives of network externalities and social presence : the mediation effect of perceived benefit / Mahsa Omidi - Omidi, Mahsa (2012)
Online social networking sites membership and usage is growing around the world, breaking the borders among the countries and becoming a global phenomenon. Individuals with common interests, from different social groups such as family, school and friendship are now able to be connected to each other via this computer mediated interaction channel. Facebook is one of the most popular sites. The exponential growth in their user base makes it important to investigate a better understanding on factors contributing in intention to use these websites and continue the usage. In this paper we try to examine some factors affecting users’ continuance intention to use (CIU) social networks. This study examines the intention to use social networks from perspectives of network externalities (number of peers and perceived complementarity) and social presence. Furthermore, the mediation effect of perceived benefit (usefulness and enjoyment) is going to be tested. Correlation and regression methods were used to test the hypotheses and mediation effect. Based on the findings, usefulness had the highest effect on intention to use followed by social presence, perceived complementarity, enjoyment, and lastly number of peers. Perceived benefit mediated the relationship between network externalities and continuance intention to use completely but for social presence the mediation effect was moderate and not supported completely. We also examined the relationshipof factors affecting social network usage with continuance intention to use for men and women separately. Findings indicate that number of peers has no relationship with CIU for men. Another difference between genders was enjoyment. Women intention to use social networks is not related to enjoyment experience, which instead is a relatively important factor for men.Findings, discussions and implications of this study can be useful for social network service providers, marketers and active online commercial participants.